Advertising self-regulation and complaints: a comparative study in Portugal and Spain - Estrela, R.; Loureiro, S. M. C. (South Asian Journal of Marketing and Management Research, 2013)
This paper aims to make an analysis of the present situation of advertising self-regulation in Portugal and Spain. For such we compared data provided by the Portuguese institute of advertising self-regulation (ICAP) with data from AutoControl (Spanish self-regulatory body) of Spain. We also conducted an in-depth individual interview. Portugal shows fewer complaints, which may indicate less informed or demanding consumers, and which clearly demonstrates that the Spanish consumer associations resort to their self-regulatory body to solve cases of illegal advertising. Official entities should be awake for the research results in order develop campaigns to raise awareness among consumers for the negative consequences of the illegal and no ethics advertising in the consumer’s life.